Gout in Pregnancy: A Rare Phenomenon - Pierre, Kevin (Cureus, 2020)
Gout is a rare phenomenon in reproductive age women due to the uricosuric effects of estrogen. Furthermore, gout in pregnancy has been reported in only a scant number of case reports. We present the case of a 21-year-old gravida-4 para-3 female at four-weeks gestation presenting with acute polyarticular gout, complicated by Haemophilus influenzae sepsis and hyperemesis gravidarum. The gout flare was likely precipitated by primary H. influenzae bacteremia, which was successfully treated with intravenous antibiotics. The treatment of gout in pregnancy is challenging because of the limited number of guidelines. We demonstrate successful management of an acute gout flare in pregnancy with colchicine and steroid injection of the affected joint. Unfortunately, the patient suffered a miscarriage, but the link between gout flare and spontaneous abortion is tenuous.